Analisis Buku Teks Sejarah Kelas X Kurikulum 2013 - Beril Choliq Arraman; Nahdatul Hazmi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2018)
The research aims at analyzing text book content in curriculum 2013. The research used qualitative approach. the techniques to collect the data were library study, reading and analyze the whole data in primary data. The finding presented that the text book for senior high school grade X curriculum 2013 was in 'proper' category including proper content and language. However, the notes in the graphic aspect were it needed to be fixed so that the students may understand the content for each chapter easier. Another weakness was there were some parts in the chapter that did not present the supporting material. However, the content has met the standard of BSNP. Finally, content proper, graphic, language, and presentation of the book has met the standard of BSNP. Keywords: Content Proper Analysis, Texts Book, Curriculum 2013